Perbedaan Penyembuhan Hecting Wound Tikus Putih Jantan Sprague Dawley dengan Wharton’s Jelly Dan D Gel - Mustofa Mustofa; Evy Kurniawaty; Arif Yudho Prabowo; Novita Carolia (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: Post-heating wounds are wounds that occur because of medical action, physiologically the body will experience a wound healing process. D gel is a gel containing cyclic siloxane and vitamin C that can be used for post-heating wound healing, but one of the other wound treatments that can currently be used is human umbilical cord mesenchymal stem cell extract (WJMSCs). Aim: knowing the difference in post-heating wound healing time between WJMSCs extract and D gel. Method: Using a laboratory experimental study using 21 male white rats (Rattus Copernicus) Sprague Dawley strain which was grouped into three different treatment groups. The treatments were divided into K group: negative control (povidone-iodine), P1: WJMSCs extract, and P2: D gel. Observations on post-heating wounds were carried out for 14 days using the Nagaoka criteria and the data were analyzed using categorical descriptive statistical tests and Kruskal-Wallis. Results: showed that there was a significant difference in post-heating wound healing time between WJMSC extract and D gel with p-value = 0.03, with wound healing time in group K: 12.7 days, group P1: 7 days, and group P2: 11 days. Conclusion: that there is a significant difference in post-heating wound healing between WJMSC extract and D gel